2011
DOI: 10.1007/s00430-011-0192-3
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi antigen immunization induces a higher B cell survival in BALB/c mice, a susceptible strain, compared to C57BL/6 B lymphocytes, a resistant strain to cardiac autoimmunity

Abstract: Chagas disease, caused by Trypanosoma cruzi, is endemic in Latin America and represents the most common infectious myocarditis worldwide. Autoimmunity is one of the mechanisms contributing to its pathogenesis. Although the cellular interactions that promote this autoimmune response are still poorly understood, several studies have demonstrated a key role for B lymphocytes since they secrete antibodies, cytokines and present antigens. Recently, we reported that immunization with cruzipain, an immunodominant T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The innate immune system has the ability to sense pathogens via germ line–encoded pattern recognition receptors. These receptors recognize pathogen associated molecular patterns (PAMPs), conserved molecules shared by several microorganisms, including T. cruzi, and trigger the activation of host innate responses 2–4 . Adaptive immunity to T. cruzi has been well characterized, with critical involvement of CD4 + Th1 and CD8 + T cells that recognize T. cruzi –specific antigens 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The innate immune system has the ability to sense pathogens via germ line–encoded pattern recognition receptors. These receptors recognize pathogen associated molecular patterns (PAMPs), conserved molecules shared by several microorganisms, including T. cruzi, and trigger the activation of host innate responses 2–4 . Adaptive immunity to T. cruzi has been well characterized, with critical involvement of CD4 + Th1 and CD8 + T cells that recognize T. cruzi –specific antigens 2 .…”
Section: Introductionmentioning
confidence: 99%
“…These receptors recognize pathogen associated molecular patterns (PAMPs), conserved molecules shared by several microorganisms, including T. cruzi, and trigger the activation of host innate responses. [2][3][4] Adaptive immunity to T. cruzi has been well characterized, with critical involvement of CD4 + Th1 and CD8 + T cells that recognize T. cruzispecific antigens. 2 However, it is still unknown to what extent the absence of adaptive immunity influences neuroendorine responses triggered by T. cruzi inoculation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the divergence between low parasite load in the tissue and severity of the lesions observed during the chronic phase reinforces the hypothesis that other factors than the immune response developed against the parasite might be involved in the development of Chagas pathology [19]. In this context, humoral and cellular autoimmune mechanisms are developed during Chagas disease [20][21][22][23]. Autoimmune mechanisms triggered during infection by T. cruzi may occur after bystander activation, parasite-cardiomyocyte harm, or molecular mimicry [24].…”
Section: Chagas Disease: An Outburst Of Inflammatory Events That May mentioning
confidence: 58%
“…In CRZ immunization, increased survival rate of B cells with increased IL-4 production in BALB/c (susceptible to cardiac autoimmunity) compared to C57BL/6 mice (resistant), was observed. The investigators concluded that CRZ immunization contributed in increasing host autoimmunity [147] . The role of attenuated Salmonella enterica, as a delivery system, carrying plasmid encoding CRZ was investigated.…”
Section: Applicationsmentioning
confidence: 99%